Genetic diversity, morphological and quality traits of Momordica dioica - Lalu Prasad Yadav; K. Gangadhara; A. K. Singh; D. S. Mishra; Vikas Yadav; Jagadish Rane; S. K. Malhotra; Prashant Kaushik; Dinesh Jinger; N. K. Meena; V. V. Apparao; Hanuman Ram (Scientific Reports)
Abstract The goal of the current study was to assess genetic variability in Momordica dioica for both qualitative and morphological features to create trait-specific lines. The correlation coefficients among twenty-three different traits of twenty-one Momordica dioica gynoecious accessions calculated and summarized by using the best linear unbiased predictor (BLUPs). The traits contribution to principal components for growth, yield and yield attributing characters positively contributed towards the PC-I were tender fruit weight (FWT), mature fruit weight (FWM), ripen fruit weight (FWR), fruit yield per plant (MFYP), fruit yield per hectare (MFPH), seeds per fruit (NSF), fruit length (FL), fruit diameter (FD), inter-nodal length (IL), fruit pedicel length (FPL), leaf width (LW), leaf length (LL) and vine length (VL). Three groups were identified; group III had the most genotypes (10), followed by cluster II (07), and cluster I (04). Group II and III had the greatest inter-cluster value (8.73811), proceeded by group III and group I (8.738105) which indicates a wider genetic base among the genotypes under study. For the twenty-three traits, different genetic traits were analyzed, including heritability (H2), genetic advance (GA), genetic advance as a percentage of mean (GAM), and phenotypic coefficient of variability and genotypic coefficient of variability (PCV & GCV). High PCV and GCV were noted respectively for the VL (26.93 and 26.24), number of stems per plant (28.12 and 21.03), LL (23.60 and 23.48), LW (21.21 and 21.09), FPL (37.53 and 36.74), FL (22.06 and 21.75), FD (22.65 and 22.60), FWT (39.77 and 49.76), FWM (51.07 and 51.01), FWR (51.97 and 51.79), fruits per plant (51.97 and 51.79), NSF (22.99 and 21.06), 100 Seed weight (141.25 and 141.25), MFYP (54.14 and 53.94) and MFYH (54.13 and 53.93). High GA as per cent grand mean was observed for VL (73.59%), number stem per plant (23.76%), FL (22.01%), FD (23.40%), FWT (24.07%), NFP (99.70%), 100 Seed weight (25.55%), MFYP (21.14%), MFYH (28.55%) and ascorbic acid (115.58%). The study provided a comprehensive of genetic variability of Momordica dioica for morphological and qualitative traits to support the development of gynoecious lines with specific traits.